2023
DOI: 10.1101/2023.08.04.23293152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Four Models of Wastewater-Based Surveillance for SARS-CoV-2 in Jail Settings: How Monitoring Wastewater Complements Individual Screening

Abstract: ObjectiveTo describe four unique models of implementing Wastewater Based Surveillance (WBS) for SARS-CoV-2 in jails of graduated sizes and differing architectural designs.MethodsThis study summarizes how jails of Cook County (Illinois, average daily population [ADP] 6000), Fulton County (Georgia, ADP 3000, Washington DC (ADP 1600) and Middlesex County (Massachusetts, ADP 875) initiated WBS between 2020 and 2023.ResultsPositive signal for SARS-CoV-2 via WBS can herald new onset of infection in a previously unin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…FCJ was one of the sites in the program. Later that year, with funding from the Bill & Melinda Gates Foundation, the Center for the Health of Incarcerated Persons (CHIP) at Emory University and Northwell Health (New Hyde Park, NY) began the SWANSS implementation study of self-collected nasal swab collection of specimens for PCR testing in tandem with WBS [13]. Opt-out nasal swab screening by laboratory-based PCR was conducted from October 2021-May 2022 on a weekly basis, in randomly chosen housing units, averaging 300 tests per week.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…FCJ was one of the sites in the program. Later that year, with funding from the Bill & Melinda Gates Foundation, the Center for the Health of Incarcerated Persons (CHIP) at Emory University and Northwell Health (New Hyde Park, NY) began the SWANSS implementation study of self-collected nasal swab collection of specimens for PCR testing in tandem with WBS [13]. Opt-out nasal swab screening by laboratory-based PCR was conducted from October 2021-May 2022 on a weekly basis, in randomly chosen housing units, averaging 300 tests per week.…”
Section: Settingmentioning
confidence: 99%
“…WBS data can also be used in tandem with clinical testing data provided by Polymerase Chain Reaction (PCR) and antigen testing; it can hasten the response to an outbreak and guide public health decision making [10]. We have previously demonstrated that WBS combined with NST is convenient and accurate, and acceptable among residents of FCJ [12][13][14]. The rst objective of the SWANSS (Surveillance via Wastewater monitoring And Nasal Self-Collection of Specimens) study was to nd a correlation between WBS and NST in a carceral setting [14].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous use cases for how wastewater monitoring has been used by public health officials for decision-making have been demonstrated, including as an early warning system that can indicate disease trends and hospitalizations before other surveillance data (e.g. clinical testing) [1][2][3][4][5][6][7] , as a source of information on disease trends where there is limited case data 6,[8][9][10][11] , and as a tool for detecting localized outbreaks within communities [12][13][14][15][16][17][18][19][20][21] and facilities [22][23][24][25][26][27][28][29][30][31] . Another important use case for wastewater monitoring is to detect vaccine-preventable diseases and direct immunization resources.…”
Section: Introductionmentioning
confidence: 99%